2019
DOI: 10.1002/jcc.26042
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Effect on Positive Patterned Self‐Assembled Monolayer Grown from a Droplet of Alkanethiol

Abstract: Atomic force microscope technique is widely used for the spatial narrow deposition of molecules inside the bare space of preexisting self‐assembled monolayer (SAM) matrix. Using molecular dynamics simulation, we studied the formation of positively patterned SAM from a globule of 1‐octadecanethiol (ODT) on predesigned SAM matrix of 1‐dodecanethiol (DDT) and effect of temperature on it. The alkyl chains of ODT SAM were densely packed and ordered by means of chemisorption through sulfur atoms. The circular SAM of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…They reported that while the structural parameters such as the lattice constant and the tilt angle are almost independent of the type of anchoring molecule, the alkyl-chain orientation in the matrix is critically controlled by the composition and the chemical nature of the molecule. An interesting study of SAM formation was recently reported by Sannyal et al 35 They predesigned a SAM matrix of 1-dodecanethiol (DDT) and simulated the formation of a SAM island from a droplet of 245 1octadecanethiol (ODT) molecules. With the use of an united atom force field and a Morse potential to model the chemisorption interaction, they successfully simulated the formation of SAM within a short simulation time of 40 ns.…”
Section: ■ Introductionmentioning
confidence: 99%
“…They reported that while the structural parameters such as the lattice constant and the tilt angle are almost independent of the type of anchoring molecule, the alkyl-chain orientation in the matrix is critically controlled by the composition and the chemical nature of the molecule. An interesting study of SAM formation was recently reported by Sannyal et al 35 They predesigned a SAM matrix of 1-dodecanethiol (DDT) and simulated the formation of a SAM island from a droplet of 245 1octadecanethiol (ODT) molecules. With the use of an united atom force field and a Morse potential to model the chemisorption interaction, they successfully simulated the formation of SAM within a short simulation time of 40 ns.…”
Section: ■ Introductionmentioning
confidence: 99%